On Specification Predication and the derivation of copular to-clauses in Polish - Tajsner, Przemysław (Studia Anglica Posnaniensia, 2016)
The proposal advanced in the paper is confronted with three earlier accounts dealing with copular-to clauses, and is shown to avoid some empirical and conceptual problems they have posed. It is shown how the derivation of copular-to clauses proceeds through a sequence of minimal and well-defined steps starting from the formation of an array of two nominal phrases, through a Small Clause stage to a Specification Predicative Phrase. Couched in the recent minimalist framework, the analysis specifically dwells on the theoretical advancements determining the nature of syntactic derivations, such as Hornstein’s (2009) distinctions between operations Concatenate, Merge and Label, Moro’s (2000, 2008) idea of Spontaneous Symmetry Breaking or Chomsky’s (2013) view of Labeling.